Modified Methylation Following Electrostimulation in a Standardized Setting—Complementing a Transcriptomic Analysis - Biagio Di Pietro; Simona Villata; Anna Plaksienko; Tiziana Guarnieri; Simeone Dal Monego; Margherita Degasperi; Pietro Di Lena; Danilo Licastro; Claudia Angelini; Francesca Frascella; Lucia Napione; Christine Nardini (Cells)
Electrical stimulation (ES) is widely employed in both clinical therapies and research settings where it has shown promise in promoting tissue regeneration, wound healing, and inflammation control. Research has also highlighted ES as a regulator of DNA demethylation, which plays a critical role in nerve regeneration and cellular repair mechanisms. While the impact of ES on epigenetic processes is recognized, its broader effects on cellular functions, particularly in inflammation and wound healing, are less understood. We recently showed how ES impacts inflammatory states by modulating transcriptomic and metabolomic profiles in a 3Din vitromodel where human fibroblasts and keratinocytes are included in a collagen matrix, i.e., even in the absence of the nervous system. Here, we propose to deepen our exploration on the differential effects on DNA methylation, including an investigation of the correlation with age acceleration using a mitotic clock. These results confirm and caution on the differential effect of DC on inflamed and non-inflamed samples and suggest an involvement of direct current stimuli at 1 V (<semantics>DC1</semantics>) in the control of senescent processes associated with mitosis and inflammation; the mechanistic details of these will have to be clarified with additional experiments.